Ethical challenges in the relationship between nurses and transsexual people in the Primary Health Care (Research, Society and Development, 2021)
This study aimed at identifying and discussing the possible factors to hinder or weaken the relationship between nurses and transsexual patients in the Primary Health Care, with a focus on ethical and humanized conduct, as well as the influence of nurses’ moral values and self-knowledge about their difficulties in addressing such topic. This is an original, exploratory study using qualitative approach. Data were collected through semi-structured interviews applied to 12 transsexual patients from December/2018 to March/2019. Data collection took place in a district in the city of Rio de Janeiro, having started upon observing all ethical and legal aspects and regulations related to investigations with human beings in accordance with resolution No. 466, dated December 12, 2012, of the Brazilian National Health Council. The results suggest a relationship based on stigma and prejudice that interferes in the self-realization of transsexual patients – who see themselves in an environment that is sometimes hostile with the denial of basic rights – and promotes an increase in vulnerabilities and personal suffering arising from the lack of recognition. We concluded that the nurses’ self-knowledge is a key factor to establish an ethical and humanized relationship, thus providing assistance oriented to the health demands of transsexual patients.